KNOWLEDGE MANAGEMENT DAN PENGARUHNYA TERHADAP KINERJA ORGANISASI (SUATU TINJAUAN TEORITIS) - Intan Cahyani; Anwar Anwar (Ekonis: Jurnal Ekonomi dan Bisnis, 2016)
Knowledge management refers to various practices and techniques used by organizations to identifyand distribute knowledge. Knowledge is categorized into twogroups, namely explicit knowledge andtacit knowledge. The implementation of knowledge management into organizations involves threecomponents, i.e.people, process and technology. The objective of this article is to show the linkbetween knowledge management and organizational performance. Some articles show that knowledgemanagement does not quite influence the organization. This conclusion may due to the onlyknowledge management factor used as the influencing factor of performance is innovation.Keywords: knowledge management, organizational performance, tacit, explicit